GEOGRAPHIC INFORMATION SYSTEM FOR KABUPATEN PESISIR BARAT WEB BASIS TOURISM MAPPING - Resti Lucyana; Kurnia Muludi; Machudor Yusman (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Information on goegrapichal condition needed by stakeholders, such as distance information, location, required information, and other information. Geographic information system (GIS) which known sistem informasi geografis (SIG) is one of solution to aquire that geographic information. Tourism in Kabupaten Pesisir Barat is the object which become material of this research thesis. The reason is Kabupaten Pesisir Barat has good potency in tourism which present tourism destinations, not only for domestic tourist, but also international tourist. The tourism destination divided into marine tourism (wisata marina), water tourism (wisata tirta), historical tourism (wisata sejarah), and natural conservation tourism (wisata suaka alam). SIG web basis is made by using PHP programing and getting data on google maps, using waterfall method and supporting software such us GPS coordinates and Xampp server.Â Keyword: tourism, geographic information system (GIS), web